Energetic analysis on malaysian AP-N process for floating liquefaction of natural gas - Muhamad Hazman Mat Saat (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The liquefaction of the natural gas is one of the important processes in the world. Nowadays, there are many liquefaction of natural gas technology that been discovered. This is because; the human demand on the natural gas production is increasing from day to day. Now, there are many technologies that have been proposed by the scientist to increase the production of natural gas in order to fulfill the human need.